The economic burden of congenital Zika Syndrome in Brazil: an overview at 5 years and 10 years. Issue 7 (15th July 2022) - Fernandes, Silke; Pinto, Marcia; Barros, Letícia; Moreira, Maria Elisabeth Lopes; de Araújo, Thália Velho Barreto; Lyra, Tereza Maciel; Valongueiro, Sandra; Jofre-Bonet, Mireia; Kuper, Hannah
Abstract : Background: The aim of this paper is to estimate the economic burden of children with congenital Zika Syndrome (CZS) in Brazil over 5–10 years. Methods: We conducted a modelling study based on data collected in a case–control study in Brazil, including children with CZS (cases) and typically developing children (controls), born in 2015 and 2016. In total, 484 participants were recruited in two sites, Recife and Rio de Janeiro. Social and economic information was collected in a survey from the carers of cases and controls, and detailed healthcare utilisation was recorded for each child in the Rio de Janeiro cohort prospectively in a database. We used this information to estimate the cost per child with severe, moderate and no CZS and incremental cost per child with severe and moderate versus no CZS from a disaggregated societal perspective. These estimates were incorporated into an economic burden model to estimate the incremental burden of the CZS epidemic in Brazil over 5 years and 10 years. Findings: The societal cost per child with severe CZS was US$50 523 to 10 years of age (born in 2015 and 2016), substantially higher than the costs for moderate CZS (US$29 283) and without CZS (US$12 331). The incremental economic burden of severe versus no CZS in Brazil over 10 years was US$69.4 million from the household and US$129.0 million from the government perspective. For moderate CZS, these figures amounted to US$204.1 million and US$86.6 million. Over 10 years, 97% of the total societal economic cost of severe CZS is borne by the government, but only 46% for moderate CZS. Interpretation: The economic burden of CZS is high at the household, provider and government levels. The compensatory government payments helped to alleviate some of the additional costs incurred by families with a child qualifying for the disability benefits, and could be scaled to include the children with moderate CZS.